Gleanings of Freedom : Free and Slave Labor along the Mason-Dixon Line, 1790-1860 - Grivno, Max L. (Book collections on Project MUSE., 2011)
Late 18th- and early 19th-century landowners in the hinterlands of Baltimore, Maryland, cobbled together workforces from a diverse labour population of black and white apprentices, indentured servants, slaves, and hired workers. The Upper South during this period presents a unique perspective on how free and slave labour systems coexisted and interacted during a time when slavery and free labour were moving apart both geographically and ideologically. This work examines the intertwined lives of the poor whites, slaves, and free blacks who lived and worked in this wheat-producing region along the Mason-Dixon Line in the decades preceding the Civil War.